Exploring Saudi Teacher’s Readiness to Use Augmented Reality (AR) Technology to Teach English Language in Schools - ALMZIAD, AMAL ABDULLAH (Journal of Ecohumanism, 2025)
This study seeks to investigate the readiness of Saudi teachers to use augmented reality (AR) technology to enhance English language instruction in secondary schools in Riyad, Saudi Arabia. With the increasing integration of technology into educational settings, AR technology has garnered considerable attention as a potential aid for engaging and motivating language learners. Throughout this research, ten Saudi English language teachers from selected secondary schools in Riyad were interviewed to collect data. The findings consistently indicate a resoundingly positive response to AR technology, with teachers keen to incorporate it into English language classes. In addition, the study revealed that Saudi teachers recognised several significant advantages of AR technology in English language teaching. These results suggest that AR has the potential to revolutionize traditional teaching methods and improve the educational experience for both teachers and students. English language teachers in the study area are eager to adopt AR technology as an effective instrument for teaching English in secondary schools. This study catalyzes future research and collaboration to effectively integrate AR technology into the English language curriculum, thereby transforming the way English is taught and learned in Saudi Arabian secondary schools.